2006
DOI: 10.1038/ng1858
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion encompassing MAPT at chromosome 17q21.3 is associated with developmental delay and learning disability

Abstract: Recently, the application of array-based comparative genomic hybridization (array CGH) has improved rates of detection of chromosomal imbalances in individuals with mental retardation and dysmorphic features. Here, we describe three individuals with learning disability and a heterozygous deletion at chromosome 17q21.3, detected in each case by array CGH. FISH analysis demonstrated that the deletions occurred as de novo events in each individual and were between 500 kb and 650 kb in size. A recently described 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
284
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(291 citation statements)
references
References 29 publications
4
284
0
3
Order By: Relevance
“…1 A distinct MAPT haplotype, H2, in one of the parents has been suggested to be a prerequisite to facilitate the microdeletion. [5][6][7]11 The H2 haplotype is detected in 20% of the independent chromosomes, in the Utah HapMap project sample of individuals of the Northern and Western European ancestry, and is linked to an inversion polymorphism of B900 kb. 9 In family 1, the mother of the siblings is a H1/H2 heterozygote.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A distinct MAPT haplotype, H2, in one of the parents has been suggested to be a prerequisite to facilitate the microdeletion. [5][6][7]11 The H2 haplotype is detected in 20% of the independent chromosomes, in the Utah HapMap project sample of individuals of the Northern and Western European ancestry, and is linked to an inversion polymorphism of B900 kb. 9 In family 1, the mother of the siblings is a H1/H2 heterozygote.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The syndrome is caused by a recurrent 500-650 kb heterozygous deletion at chromosome 17q21.31, [5][6][7] which is thought to result from nonallelic homologous recombination (NAHR), 8 mediated by flanking low-copy repeats. The minimum critical region is 424 kb (41 046 729-41 470 954 Mb, hg18) in size 1 and encompasses four known genes, CRHR1, IMP5, MAPT, and STH, in addition to three putative genes, FLJ25168, BC018035, and LOC284058.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the medical literature identified 23 articles describing the clinical features of 81 patients with KdVS. [1][2][3][4][5]13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The syndrome can be either caused by a microdeletion in chromosomal region 17q21. 31 or by a truncating variant in the KAT8 regulatory NSL complex unit 1 (KANSL1) gene (NG_032784.1).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative haplotype, a complex inversion of the first that is found in 20% of Europeans, was shown in 2005 to correlate with larger family sizes, suggesting that this second haplotype was under some form of positive selection 7 . But in 2006, Evan Eichler 8 , a geneticist at the University of Washington in Seattle, and two other groups 9,10 showed that the inverted region was also prone to frequent spontaneous deletions that led to mental retardation. The inverted haplotype seemed to be both adaptive and the source of debilitating deletions.…”
Section: Twists and Turnsmentioning
confidence: 99%